The Influence of the CoComelon Songs in Vocabulary Mastery at 4th Grade Students of SDN Runggu - Nurmahdania Nurmahdania; Annisah Annisah; Ika Irawati (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2025)
The presence of the CoComelon channel has brought several positive impacts, especially through its English songs that help increase children's interest in learning the English language. This study was conducted to measure the effectiveness of CoComelon songs in English language learning, particularly in vocabulary mastery among fourth-grade students at SDN Runggu, Indonesia. In this research, the researcher applied a pre-experimental method using a quantitative approach. The subjects of the study were fourth-grade elementary school students aged between 10 and 11 years old. The students listened to and learned English vocabulary through selected CoComelon songs as part of the learning material. The main focus of this study is how CoComelon songs affect the English language skills of elementary school students at SDN Runggu, particularly in vocabulary usage. Data were collected through four stages: pre-test, treatment,  post-test, and data analysis. The design used in this study was a one-group post-test design. The results of this study indicate that the use of CoComelon songs in the learning process is effective in improving vocabulary mastery among fourth-grade students at SDN Runggu.